Case series of mild behavioral impairment: toward an understanding of the early stages of neurodegenerative diseases affecting behavior and cognition. (11th October 2017) - Cieslak, Alicja; Smith, Eric E.; Lysack, John; Ismail, Zahinoor
ABSTRACT: Mild behavioral impairment (MBI) is characterized by later life acquired, sustained, and impactful neuropsychiatric symptoms (NPS) of any severity that cannot be better accounted for by other formal medical and psychiatric nosology. MBI is an "at risk" state for incident cognitive decline and dementia, and for some, MBI is the index manifestation of neurodegeneration, observed in advance of cognitive impairment. Initially described in Frontotemporal Dementia (FTD), MBI evolved to describe a preclinical stage of all cause dementia, and has been operationalized in the International Society to Advance Alzheimer's Research and Treatment-Alzheimer's Association (ISTAART-AA) proposed research diagnostic criteria. Here, we describe three cases in which patients diagnosed with a variety of dementing conditions initially presented with NPS to the Cognitive Neurosciences Clinic at the University of Calgary, Canada. All patients described in our series were given a final diagnosis of dementia; the etiology supported by clinical, cognitive, and neuroimaging findings. In all three cases, the progression to dementia was preceded by NPS that meet criteria for MBI. With these examples, we are able to illustrate that MBI can represent a premonitory stage of dementia of different etiologies. These cases demonstrate early use of the MBI checklist (MBI-C). The cases presented in this series serve as examples of NPS as early manifestations of dementia. Our case examples include both FTD and AD, and demonstrate that before a diagnosis of a neurodegenerative disease is considered, often patients will be diagnosed with and treated for a psychiatric condition. These early NPS can be characterized within the domains outlined in the ISTAART-AA MBI criteria, and detected with the MBI-C, which may help clinicians consider neurodegenerative disease in the differential diagnosis of later life onset psychiatric symptomatology.